Randomized placebo-controlled trial of feline-origin Enterococcus hirae probiotic effects on preventative health and fecal microbiota composition of fostered shelter kittens - Gookin, Jody L.; Strong, Sandra J.; Bruno-Bárcena, José M.; Stauffer, Stephen H.; Williams, Shelby; Wassack, Erica; Azcarate-Peril, M. Andrea; Estrada, Marko; Seguin, Alexis; Balzer, Joerg; Davidson, Gigi (Frontiers in Veterinary Science, 2022)
Diarrhea is the second most common cause of mortality in shelter kittens. Studies examining prevention strategies in this population are lacking. Probiotics are of particular interest but studies in cats are largely limited to healthy adults or those with induced disease. Only one study in domestic cats describes the use of host-derived bacteria as a probiotic. We previously identified Enterococcus hirae as a dominant species colonizing the small intestinal mucosa in healthy shelter kittens. Oral administration of a probiotic formulation of kitten-origin E. hirae (strain 1002-2) mitigated the increase in intestinal permeability and fecal water loss resulting from experimental enteropathogenic E. coli infection in purpose-bred kittens. Based on these findings, we hypothesized that administration of kitten-origin E. hirae to weaned fostered shelter kittens could provide a measurable preventative health benefit. We conducted a randomized, placebo-controlled, blinded clinical trial to determine the impact of a freeze-dried E. hirae probiotic on body weight gain, incidence of diarrhea, carriage of potential diarrheal pathogens, and composition of the intestinal microbiota in weaned fostered shelter kittens. One-hundred thirty kittens completed the study. Fifty-eight kittens received the probiotic and 72 received the placebo. There were no significant differences in age, weight upon initiation of the study, number of days in the study, average daily gain in body weight, or weight at completion of the study. Kittens treated with E. hirae were 3.4 times less likely to develop diarrhea compared to kittens treated with placebo (odds ratio=0.294, 95% CI 0.109 to 0.792, p=0.022). A significant impact of E. hirae was not observed on the presence or abundance of 30 different bacterial, viral, protozoal, fungal, algal, and parasitic agents in feces examined by qPCR. With exception to a decrease in Megamonas, administration of the E. hirae probiotic did not alter the predominant bacterial phyla present in feces based on 16S rRNA gene amplicon sequencing. Decreased incidence of diarrhea associated with preventative administration of E. hirae to foster kittens supports a rationale for use of E. hirae for disease prevention in this young population at high risk for intestinal disease though additional studies are warranted.